Diversity of medicinal plants in different forest types at Bukit Tramuo Heritage Reserve, Bau - Selvana Eyra, Felix (Universiti Malaysia Sarawak (UNIMAS), 2022)
Medicinal plants are plants that contain medical properties in one or more of their organs. Medicinal plants are used in both traditional and modern healing. Although medicinal plants are the oldest form of medicine, there is less documentation about the medicinal plants as they are passed down through generations informally. This study was carried out in two different forest types, which are primary forest and secondary forest. Data analyzed established medicinal plant distribution and plant diversity along with the medicinal usage, parts used, treatment, and preparation methods. There were 18 species of medicinal plants from 9 families recorded from both forest types. The diversity index (H=) of medicinal plants in the primary forest was 1.8890 and the diversity index (H=) of medicinal plants in the secondary forest was 1.4844. The independent T-test results show no significant difference between the diversity index of medicinal plants in secondary and primary forests. Even so, both forests consist of valuable medicinal plants and should be preserved.